Modelagem da biomassa acima do solo (BAS), por meio de imagens de alta resolução espacial e índices de vegetação - Macedo, Fabrício Lopes de [UNESP] (2014)
Estimating Above Ground Biomass (BAS), with high accuracy, using remote sensing data is a current challenge. The objective of this study was to develop a function to estimate BAS in local and regional level, through images of high spatial resolution, for Quercus rotundifolia and Eucalyptus, an area in the Alentejo region of southern Portugal and Selvíria - MS, located in the region central Brazil, respectively. To this end, some empirical models were generated by combining the values of biomass estimated from inventory plots with some vegetation indices based on QuickBird image and Pleiades. Analyzing the study area 1, the model that best fit the estimation of biomass was associated with the Index Normalized Difference Vegetation index (NDVI), with a coefficient of determination (R 2 ) 75.6%. In study area 2, the models that best fit the biomass estimates made using the Soil Adjusted Vegetation (SAVI) Index, with a coefficient of determination (R 2 ) of 64.8%. These functions can be used in other regions for the same species with similar climate and with the same local features. This approach can be used as an inexpensive tool to produce estimates of biomass above ground primary local and regional scale